Review of chloride and sulphate attenuation in ground water nearby solid‐waste landfill sites - Venkatesan, G.; Swaminathan, G. (Journal of Environmental Engineering and Landscape Management, 2009)
Paper review "Review of chloride and sulphate attenuation in ground water nearby solid‐waste landfill sites". Journal of Environmental Engineering and Landscape Management 17(1): Ia-Ig. Ground water drawn for various purposes, such as irrigation, drinking and industrial, is constantly on the rise in areas where surface water are sources nowadays scarce due to erratic rainfall and climatic conditions. Chloride and sulphate in ground water increase due to municipal and industrial waste dumped on the ground surface. Elevated concentration of chloride (Cl-) and sulphate (SO4-) in surface and ground water are common in all countries, and can serve as indicators of ground water pollution. We have to characterize the most prevalent natural and anthropogenic sources of chloride and sulphate in ground water and explore techniques that could be used to identify their source. There is an urgent need for additional solid-waste management capacity sites in many parts of developing countries. Current design, operation, closure, and post-closure activities for sanitary landfills do not guarantee sufficient public health and environmental protection of the groundwater resources near a landfill. While in the past, sanitary landfills have almost without exception contaminated ground waters in the vicinity of a landfill. Due to scarcity of hand, to many urban localities, people never mind having residents near by a landfill site. Significant changes must be made in the approach used for landfill of metropolitan solid wastes. Chloride and sulphate may be taken as critical parameters in assessment of ground water quality. Chloridų ir sulfatų mažinimo požeminiame vandenyje šalia sąvartynų problemos Santrauka. Rajonuose, kur paviršinio vandens dėl kritulių nepastovumo ir klimatinių sąlygų nepakanka, yra pakilęs požeminio vandens, naudojamo drėkinimui, gėrimui, pramonėje, lygis. Dėl komunalinių ir pramoninių atliekų sąvartynų požeminiame vandenyje padaugėja chloridų (Cl–) ir sulfatų (SO4–). Jų koncentracijų padidėjimas paviršiniame ir požeminiame vandenyje dažnas visose šalyse, tuo galima remtis kaip požeminio vandens taršos indikatoriumi. Turime apibūdinti labiausiai paplitusius natūralius ir antropogeninius chloridų ir sulfatų šaltinius, teršiančius požeminį vandenį, ir ištirti metodus, kuriuos galima būtų taikyti šaltiniams nustatyti. Daugelyje besivystančių šalių būtinos papildomos atliekų tvarkymo vietos. Dabartinis komunalinių atliekų sąvartynų projektavimas, eksploatavimas, uždarymas ir atkūrimas negarantuoja pakankamos požeminio vandens išteklių apsaugos sąvartynų įtakos zonoje gyvenančių žmonių sveikatos ir aplinkos atžvilgiais. Praeityje komunalinių atliekų sąvartynai, beveik visi be išimties, teršė požeminį vandenį toje teritorijoje. Dėl patirties stokos daugelyje urbanizuotų teritorijų nekreipta dėmesio į gyvenančius netoliese. Reikšmingi pokyčiai turi būti padaryti dėl sąvartynų, kuriuose šalinamos didmiesčių atliekos, tvarkymo. Chloridų ir sulfatų kiekiai gali būti laikomi kritiniais parametrais požeminio vandens kokybei vertinti. Reikšminiai žodžiai: požeminis vanduo, chloridai, užkastos atliekos, sulfatai, atliekos. Уменьшениe хлоридов и сульфатов в подземных водах вблизи свалок Резюме. Потребляемость подземной воды для полива, питья, промышленных нужд увеличена в тех районах, в которых поверхностной воды не достаточно из-за непериодических осадков и климатических условий. В таких водах количество хлоридов и сульфатов оказывается увеличенным из-за коммунальных и промышленных отходов на свалках. Увеличение концентраций хлоридов (Cl–) и сульфатов (SO4–) вповерхностныхиподземныхводах – явление, часто наблюдаемое во всех странах. Этот фактор может рассматриваться как индикатор загрязненностиподземнойводы. Авторы стать и ставили целью охарактеризовать наиболее распространенные естественные и антропогенные источники хлоридов и сульфатов, загрязняющих подземные воды, и исследовать методы, которые могут применяться для очищения таких источников. Во многих развивающихся странах необходимо обору-дование дополнительных мест для отходов. Современные способы проектирования, эксплуатации, закрытия и открытия новых мест свалок не гарантируют достаточную защиту источников подземных вод в зоне свалок относительно здоровья людей и охраны окружающей среды. Особое внимание должно уделяться свалкам, на которые вывозятся отходы из больших городов. Хлориды и сульфаты могут использоваться в качестве критических параметров для оценки качества подземных вод. Ключевые слова: подземныеводы, хлориды, свалки, сульфаты, отходы. First Published Online: 14 Oct 2010